Pengaruh Profitabilitas, Ukuran Perusahaan, dan Kepemilikan Asing pada Pengungkapan CSR - Elma Kardiyanti, Ni Kadek; Ngurah Bagus Dwirandra, A. A. (E-Jurnal Akuntansi, 2020)
CSR Disclosure is accountability of company management to stakeholders. Profitability and Company Size is influence CSR disclosure because it is a form of positive signal to stakeholders. Finally, foreign ownership is considered as a party that has awareness of CSR disclosures. This study aims to obtain empirical evidence about the effect of profitability, company size, and foreign ownership on CSR disclosures for the period of 2016 - 2018, with a sample of 84 companies. Testing using Multiple Linear Regression and Classic Asumption Test. The test results show that the profitability and size of the company have a positive and significant effect on CSR disclosure. However, foreign ownership has no effect on CSR disclosure. Keywords: Probability; Company Size; Foreign Ownership; CSR Disclosure.